2022
DOI: 10.1016/j.xpro.2021.101034
|View full text |Cite
|
Sign up to set email alerts
|

MATISSE: An analysis protocol for combining imaging mass cytometry with fluorescence microscopy to generate single-cell data

Abstract: Summary Exploring tissue heterogeneity on a single-cell level by imaging mass cytometry (IMC) remains challenging because of its limiting resolution. We previously demonstrated that combining higher resolution fluorescence with IMC data in the analysis pipeline resulted in high-quality single-cell segmentation. Here, we provide a step-by-step workflow of this MATISSE pipeline, including instructions regarding the staining procedure, and the analysis route to generate single-cell data. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
(3 reference statements)
0
16
0
Order By: Relevance
“…In recent years, the development of multiplex imaging technologies has increased the need for methods to analyze imaging data, particularly spatial single-cell analysis. Im-ageJ [86] is the major open-source software package used for many different image analysis tasks, including single-cell segmentation, tumor grading of clinical images originating from magnetic resonance imaging (MRI), or staining quantification [87][88][89]. A more recent open-source software package specifically developed for tissue analysis, QuPath [90], is now being applied to multiple spatial tissue analysis tasks, including region annotation, cell segmentation, marker expression, and distance calculation.…”
Section: Challenges and Developments In Spatial Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the development of multiplex imaging technologies has increased the need for methods to analyze imaging data, particularly spatial single-cell analysis. Im-ageJ [86] is the major open-source software package used for many different image analysis tasks, including single-cell segmentation, tumor grading of clinical images originating from magnetic resonance imaging (MRI), or staining quantification [87][88][89]. A more recent open-source software package specifically developed for tissue analysis, QuPath [90], is now being applied to multiple spatial tissue analysis tasks, including region annotation, cell segmentation, marker expression, and distance calculation.…”
Section: Challenges and Developments In Spatial Data Analysismentioning
confidence: 99%
“…These algorithms include user-guided machine learning pipelines with Illastik [92] and CellProfiler [93]. These pipelines have been used in the analysis of datasets that combine IMC and fluorescent microscopy [16,89,91]. More recently, deep-learning algorithms that use convolutional neural networks (CNNs) have become available; these include DeepCell [17,94], U-NET [95], and DeepImageJ [96].…”
Section: Cell Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). Using the MATISSE cell segmentation pipeline that simultaneously takes advantage of highresolution DAPI nuclear imaging in combination with high-multiplexity IMC, 22,23 we identified 215,293 single cells across all patient samples. After removal of cells from excluded tissue regions (including artefacts, lymphoid follicles and submucosa), 184,975 single cells remained for data normalization, scaling and lineage determination.…”
Section: Cd8 + T Cells Are the Dominant Immune Cell Population In αPd...mentioning
confidence: 99%
“…There are a number of published "end to end" pipelines for IMC data analysis (8)(9)(10)(11)(12) that utilise open source software for segmentation such as Ilastik (13) and CellProfiler (14,15), as well as StarDist (16) and IMC-specific approaches that utilise deep learning (17). There have also been attempts to use matched fluorescent images of the nuclei using DAPI co-staining to improve segmentation accuracy (18) as well as removing image noise (19,20). Nonetheless, it has been shown that, due to the nature of tissue imaging, simple approaches to single cell segmentation are often highly effective (21).…”
Section: Introductionmentioning
confidence: 99%